KEWAJIBAN AYAH DALAM MENAFKAHI ISTRI DAN ANAK PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Niffilayani, Anita (Program Studi Hukum Keluarga Islam, Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2025)
Support is the primary obligation of a father as head of the family, both from the perspective of Islamic law and Indonesian positive law. This obligation is affirmed through the Qur'an, Hadith, classical Islamic jurisprudence, and laws and regulations, including Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI). This study aims to examine the normative basis of the obligation to provide support, along with its implementation in religious court practice in Indonesia. The method used is normative legal research with a literature approach, referring to published scientific journals, Islamic jurisprudence books, and related regulations. The results of the study indicate that the obligation to provide support for one's wife and children is absolute, remains in effect even in the event of divorce, and must be adjusted to the father's economic capacity and the children's needs. The court plays a crucial role in determining the amount of support to achieve justice and family welfare. This study emphasizes the harmonization of sharia principles, positive law, and judicial practice as the basis for enforcing the right to support